Educating scientists and engineers for academic and non-academic career success - Speight, James G. (xCRC Press, 2015)
This text focuses on the structure of the current educational system and describes the transformations needed to ensure the adequate education of future science and engineering students. It describes how university faculty can make the necessary changes to teach a broader range of skills, technical proficiency, teamwork, adaptability, and versatility within the undergraduate and postgraduate curriculum. Also covered are approaches to provide a broader exposure to experiences desired by both academic and non-university employers to prepare students for an increasingly interdisciplinary, collaborative, and global job market